ICAM3 mediates inflammatory signaling to promote cancer cell stemness. (28th May 2018) - Shen, Wenzhi; Xie, Junling; Zhao, Shuangtao; Du, Renle; Luo, Xiaohe; He, Huiwen; Jiang, Shan; Hao, Na; Chen, Chong; Guo, Chunlei; Liu, Yanhua; Chen, Yanan; et al.
Abstract: In this study, we present a medium throughput siRNA screen platform to identify inflammation genes that regulate cancer cell stemness. We identified several novel candidates that decrease OCT4 expression and reduce the ALDH + subpopulation both of which are characteristic of stemness. Furthermore, one of the novel candidates ICAM3 up-regulates in the ALDH + subpopulation, the side population and the developed spheres. ICAM3 knockdown reduces the side population, sphere formation and chemo-resistance in MDA-MB-231 human breast cancer cells and A549 lung cancer cells. In addition, mice bearing MDA-MB-231-shICAM3 cells develop smaller tumors and fewer lung metastases versus control. Interestingly, ICAM3 recruits and binds to Src by the YLPL motif in its intracellular domain which further activates the PI3K-AKT phosphorylation cascades. The activated p-AKT enhances SOX2 and OCT4 activity and thereby maintains cancer cell stemness. Meanwhile, the p-AKT facilitated p50 nuclear translocation/activation enhances p50 feedback and thereby promotes ICAM3 expression by binding to the ICAM3 promoter region. On this basis, Src and PI3K inhibitors suppress ICAM3-mediated signaling pathways and reduce chemo-resistance which results in tumor growth suppression in vitro and in vivo . In summary, we identify a potential CSC regulator and suggest a novel mechanism by which ICAM3 governs cancer cell stemness and inflammation. Highlights: We performed a high throughput siRNA screen, identified ICAM3 was an inflammation gene that regulate cancer cell stemness. ICAM3 was up-regulatedin several cancer types and correlated with tumor grades. ICAM3 was proved to recruit Src through YLPLmotif further to govern cancer inflammation and cancer cell stemness in vitro and in vivo . ICAM3 facilitated p50 nuclear translocationenhances p50 feedback to bind ICAM3 promoterthereby promotes ICAM3 expression. Inhibitors targeted Src or PI3K reduced chemo-resistance that ICAM3 mediated.